Ordering goods and services online in South East European countries: Comparison by cluster analysis - Blagica Novkovska; Ksenija Dumicic (UTMS Journal of Economics, 2019)
Extent of online purchases of goods and services is nowadays rapidly growing part of the modern economy. It is connected to rapid changes in the commerce as well as in the way of life of entire population. In this paper the influence of important factors on online purchases in South East European countries in comparison with EU-28 countries is studied. Using selected ordinary least square model it has been shown that there is a strong dependence of the percentage of individuals who use the internet for ordering goods or services on the level of internet access for households and on the percentage of individuals aged 16-74, who have basic or above basic overall digital skills. Based on cluster analysis it is identified that countries of the region recognised candidates for future membership of the European Union (ME, MK, TR, RS) demonstrate similar development patterns as other countries from the region that are already EU member states (RO, HR, BG). It can be expected in future online purchase to contribute significantly to the acceleration of economic growth of these group of countries.
Keywords: C38; C53; L81; L86; 330; digitalization; online purchases; e-commerce; digital skills